2012
DOI: 10.1186/1476-511x-11-41
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference following high cholesterol diet induced renal injury and the protective role of rutin and ascorbic acid combination in Wistar albino rats

Abstract: BackgroundAn increased interest is given to the impact of high fat diet on health worldwide. Abnormalities in lipid metabolism induced by high cholesterol diet (HCD) were reported to exacerbate renal diseases via oxidative stress pathways. Rutin and ascorbic acid showed a protective role against oxidative stress-mediated diseases. Furthermore, both lipid metabolism and tissue response to oxidative stress damage was found to vary according to animal gender. Thus, the objective of this work was to examine possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Experimental diets were prepared in pellet form by adding 0.2% rutin (RT) [41] (power, sigma, USA) or 1% cholesterol + 0.5% cholic acid (HCD) [42] or 0.2% RT + 1% cholesterol + 0.5% cholic acid (RT+HCD) in rat chow powder. Rat chow was used as normal diets and was prepared weekly and shade dried.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental diets were prepared in pellet form by adding 0.2% rutin (RT) [41] (power, sigma, USA) or 1% cholesterol + 0.5% cholic acid (HCD) [42] or 0.2% RT + 1% cholesterol + 0.5% cholic acid (RT+HCD) in rat chow powder. Rat chow was used as normal diets and was prepared weekly and shade dried.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, rutin exerts cytoprotective effects on cells exposed to various types of radiation by substantially increasing their viability [79]. So far, the interaction of orally administered rutin with ascorbic acid has been demonstrated in terms of their antiinflammatory and vascular sealing actions [4,51]. Moreover, it has been demonstrated that rutin increases the organic reduction ability of ascorbic acid [2].…”
Section: Introductionmentioning
confidence: 99%
“…d-Galactose has been used to induce oxidative stress in vivo to mimic the natural aging process in rats and mice (17)(18)(19)(20). In addition, a high-fat diet (HFD) was found to be a significant risk factor for kidney disease (21)(22)(23). HFD-induced obesity may expedite the aging process (24).…”
Section: J Nutr Scimentioning
confidence: 99%